2014
DOI: 10.1088/1751-8113/47/25/255202
|View full text |Cite
|
Sign up to set email alerts
|

Universal microscopic correlation functions for products of truncated unitary matrices

Abstract: We investigate the spectral properties of the product of M complex non-Hermitian random matrices that are obtained by removing L rows and columns of larger unitary random matrices uniformly distributed on the group U (N + L). Such matrices are called truncated unitary matrices or random contractions. We first derive the joint probability distribution for the complex eigenvalues of the product matrix for fixed N, L, and M , given by a standard determinantal point process in the complex plane. The weight however… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 70 publications
2
86
0
Order By: Relevance
“…A similar determinantal structure holds for the eigenvalues of products of truncated unitary matrices [3]. The determinantal structure opens up the way to a more detailed analysis at the finite n level [3,6].…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 72%
See 2 more Smart Citations
“…A similar determinantal structure holds for the eigenvalues of products of truncated unitary matrices [3]. The determinantal structure opens up the way to a more detailed analysis at the finite n level [3,6].…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 72%
“…A similar determinantal structure holds for the eigenvalues of products of truncated unitary matrices [3]. The determinantal structure opens up the way to a more detailed analysis at the finite n level [3,6]. Very recently, Akemann, Kieburg, and Wei [5] found that the squared singular values of products of complex Ginibre matrices are a determinantal point process on the positive real line.…”
Section: Products Of Ginibre Random Matricesmentioning
confidence: 76%
See 1 more Smart Citation
“…We note that the density (4.35) is the same as for products of truncated unitary matrices [5,1]. In fact, as suggested in [5], the validity of (4.35) can be proven using techniques from free probability; figure 1 shows a comparison with numerical data.…”
Section: Asymptotic Behaviour Of General Mmentioning
confidence: 74%
“…We will now look at asymptotic properties and we will start with the m = 1 case which is the simplest by far. This simplicity, first identified in [24], is due to the simple form of the weights w (1) r and w (1) c . Thus, it follows from (1.10) and (1.14) that w (1)…”
Section: Eigenvalue Densitymentioning
confidence: 99%